Editor's Note - Isa, Che Ruhana; Sulaiman, Ainin; Chan, Wai Ming (Asian Journal of Business and Accounting, 2016)
It is our pleasure to present you with the second issue of Volume 9 of the Asian Journal of Business and Accounting (AJBA). AJBA made its debut in 2008 and is currently indexed in the Emerging Sources of Citation Index (ESCI), SCOPUS, ERA 2012, Asean Citation Index and MyCite. In recognition of AJBA’s excellent performance, the Malaysian Ministry of Higher Education conferred AJBA with the status of CREAM 2016 on 1 November 2016. Given the rigour and the quality of papers that have been published and are currently under review, we are hopeful that AJBA will soon succeed in its endeavour to be indexed in the Social Science Citation Index. For this issue, we have selected six papers authored by researchers from Indonesia, Jordan, Malaysia, Pakistan, Thailand, and the United Arab Emirates. The papers cover a wide range of areas in business and accounting with a focus on sustainability. We hope that the findings and discussions drawn from these papers will promote better business decision-making processes and an effective formulation of public policies in Asia. For a business to sustain, there must be adequate capital. Using the system Generalized Method of Moments, Ying, Albaity, and Zainir analyse the data of Chinese industrial and consumer firms from 2008 to 2013. They find that the adjustment speed of dynamic capital decision is faster in consumer firms than in industrial firms. They also observe differences in the total and long term debts of firms from these two sectors as well as the determinants of their capital structure. The results provide insights into one of the largest economies in the world. One method to raise capital for businesses is through the issuance of bonds. In their paper, Utama, Utama, and Amin investigate the influence of corporate governance practices and ownership structure on the credit ratings of listed firms in Indonesia, a large emerging economy. Their findings suggest that firms tend to have better credit ratings and more access to long term debts if they conduct best practices of corporate governance. Accounting standards and auditing are crucial issues in corporate governance. The paper by Bangmek, Lonkani, Tangeakchit, and Sarapaivanich analyse Thai data. They find that accounting conservatism enhances the value of voluntary disclosure information. This study is timely as the International Accounting Standards Board (IASB) has proposed, in 2015, to reintroduce the concept of conservatism as a means of increasing the usefulness of financial statements to investors. Some of the financial reporting standards introduced by the IASB require the use of fair value estimates. Using semi-structured interviews with experienced Jordanian auditors, the paper by Abdullatif reveals that Jordanian auditors find it a challenge to audit fair value estimates in an environment that has limited reliable fair value information, a low demand for high quality audits and which suffers from weak corporate governance, in general. A discourse on the sustainability of business is not complete without venturing into the area of firms’ financial performance. The paper by Ashraf, Jaafar, and Sulaiman focuses on online product recommendations (“OPRs”). To enhance sales and thus, their financial performance, e-retailers equip their sites with OPRs so as to provide product recommendations to potential customers. Hence, it is important for customers to be satisfied with OPRs use. Analysing the responses of existing OPR users, Ashraf et al. find that perceived ease of use, usefulness and confirmation are significant contributors to customer satisfaction with OPRs. In the final paper, Suwannarat concentrates on export intermediaries which play an important role in enabling exporters to enter a wider overseas market. Analysing data drawn from Thai export intermediary firms, he finds that firm’s resources and competency to reduce clients’ transaction costs have a positive impact on their performance. The guidance of the members of the editorial and advisory board and the contributions of the reviewers play a crucial role in enhancing the performance of AJBA. Likewise, the financial support from the Malaysian Accountancy Research and Education Foundation is also necessary in sustaining the journal. As the year 2016 draws to a close, we wish to say a big ‘Thank You’ to them. Thank you, and have a great 2017!